Electrical and optical characterization of Pd/ZnO nanorods (NRs) Schottky diodes grown on n-Si substrates - Somvanshi D.; Jit S. (My University, 2025)
We report the electrical characteristics of Pd/ZnO nanorods (NRs) Schottky diodes grown on n-Si substrates by simple thermal evaporation technique. As-grown ZnO NRs have excellent surface morphology and grown vertically to the substrates surface. Thermionic emission (TE) model and Norde methods have been applied for the determination of different electrical parameters of the Pd/ZnO NRs Schottky diode at room temperature. A good value of barrier height (φB,eff)∼0.81 eV, ideality factor (η) ∼1.46 and series resistance (Rs) ∼412 kΩ have been evaluated from ln I-V and F(V) -V plot. The Pd/ZnO NRs Schottky diode find their application in nanophotonics. © 2014 AIP Publishing LLC.